Privacy Compliance System by Design Platforms: A Case of Privacy Concerns for Thai Teenagers - Saetang, Saranya (Journal of Applied Informatics and Technology, 2021)
The concern over privacy is growing, and several attempts have been made to address privacy invasion and suggest privacy ethics in technology design. However, users' privacy is still customized by the technology around them. Teenagers who are technology savvy are often not aware of online privacy as much as adults. Therefore, their privacy was customized by the Internet or technology devices around them especially via their mobile phone. This study aims to present a design guideline for privacy compliance system by reviewing previous design platforms, and identifying the most concerns of privacy invasions for users and how they react to those invasions. From the legal and designer perspectives, the developer should consider privacy principles of system design, namely, notice/awareness, choice/consent, access/participation, security, enforcement/redress and anonymity/pseudonymity. By using open-ended questionnaires which were sent to 42 Thai teenagers, the results show that the most privacy invasion that students concerned is advertising via mobile phone messages. This invasion could cause annoyance and a waste of time and money. The teenagers react to the invasion varied from calling to the wireless service provider to help stopping those advertisements, blocking the intruders and finally, stopping the use of those services or applications. It was also found that teenagers are concerned only for the privacy invasions that interrupt while they were using the Internet applications, but they have less concern over the collection of their personal information. At the end of this study, some practical implications are suggested as guidelines for a privacy compliance system.